2023
DOI: 10.1097/js9.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics study in screening and differential diagnosis of multiple primary lung cancer

Abstract: Background: Multiple primary lung cancer (MPLC) is becoming increasingly common in clinical practice. Imaging examination is sometimes difficult to differentiate from intrapulmonary metastasis (IM) or single primary lung cancer (SPLC) before surgery. There is a lack of effective blood biomarkers as an auxiliary diagnostic method. Participants and Methods A total of 179 patients who were hospitalized and operated in our department from January to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Specifically, we are concerned about the potential impact of differences in pathological stage and tumor grade between groups, which were not accounted for in the study. As shown in 1 , there were significant differences in pathological stage ( P =0.027) and tumor grade ( P =0.014) between the groups. Therefore, the differences observed in plasma metabolomics may have been caused by differences in these variables rather than the group differences between MPLC, intrapulmonary metastasis (IM), and synchronous primary lung cancer (SPLC).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Specifically, we are concerned about the potential impact of differences in pathological stage and tumor grade between groups, which were not accounted for in the study. As shown in 1 , there were significant differences in pathological stage ( P =0.027) and tumor grade ( P =0.014) between the groups. Therefore, the differences observed in plasma metabolomics may have been caused by differences in these variables rather than the group differences between MPLC, intrapulmonary metastasis (IM), and synchronous primary lung cancer (SPLC).…”
mentioning
confidence: 79%
“…Secondly, the conclusions drawn in this study 1 may be flawed due to confounding variables that were not properly addressed. Specifically, we are concerned about the potential impact of differences in pathological stage and tumor grade between groups, which were not accounted for in the study.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Liu et al 4 conducted an original research to screen out metabolites with diagnostic significance as potential biomarkers for MPLC, by comparing different plasma samples from MPLC, intrapulmonary metastasis, single primary lung cancer, and healthy people. They found that there were obvious differences in the metabolite profiles among them.…”
mentioning
confidence: 99%